2010
DOI: 10.1002/pi.2924
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐ and pH‐sensitive hydrogels based on 2‐(2‐methoxyethoxy)ethyl methacrylate and methacrylic acid

Abstract: Hydrogels based on commercially available 2‐(2‐methoxyethoxy)ethyl methacrylate (MEO2MA), with methacrylic acid (MAA) as comonomer, are studied. The incorporation of an ionizable monomer, such as MAA, in a thermosensitive system leads to the formation of hydrogels able to respond to pH and temperature according to their monomeric composition. Thus, at low pH, the acid groups of MAA are protonated, and they do not contribute to increase the hydrophilic balance, and collapse of the hydrogels occurs around room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…In previous investigations, 19,20,22 it was shown that the VTT of the MEO 2 MA-based hydrogels occurred with a very fast change in the sample transparency. Thus, these hydrogels were completely transparent at low temperatures but became opaque above the transition temperature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous investigations, 19,20,22 it was shown that the VTT of the MEO 2 MA-based hydrogels occurred with a very fast change in the sample transparency. Thus, these hydrogels were completely transparent at low temperatures but became opaque above the transition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is possible that not all of the double bonds in POSS-meth 8 functioned as crosslinker points because of steric effects according to Sastre et al 35 One of the most interesting features of the MEO 2 MA-based hydrogels is their thermo-responsiveness. 19,20,22,28 Thus, the waterswelling capacity of the samples was evaluated as a function of temperature. The experimental results are collected in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations